Pengaruh Pendampingan Mpasi Terhadap WHZ Score (Studi Eksperimental pada Bayi Usia 6 hingga 10 Bulan di Desa Kedunguter dan Desa Batu, Wilayah Kerja Puskesmas Karangtengah, Kabupaten Demak) - Fauzia Shaffa Rizqya Yudianto; Sri Priyantini (PT. Hasba Edukasi Mandiri, 2026)
Stunting and wasting are chronic malnutrition problems caused by insufficient nutritional intake over a long period of time due to food that does not meet nutritional needs for height according to age, which is below -2 standard deviations. Maternal knowledge is an important factor in providing additional food to infants. This study aims to determine the effect of Complementary Feeding on WHZ Scores in Infants Aged 6 to 10 Months. Experimental research with a posttest only control group design with purposive sampling. 22 control samples were not given complementary feeding education and 22 intervention samples were given education. The study was conducted in September - November 2025. Data collection used an infantometer and scales. Data were analyzed using the Chi-Square test. The results of the study showed that an increase in nutritional status occurred more in the control group of 17 children (77.3%) compared to the intervention group of 15 children (68.2%), while no increase in nutritional status occurred in 5 children (22.7%) in the control group and 7 children (31.8%) in the intervention group. The statistical analysis results obtained p = 0.498. There was no effect of complementary feeding assistance on the WHZ score in infants aged 6 to 10 months.